Measuring PMTCT effectivenss through HIV free survival in children under 2 years - Sineke, Tembeka (Department of Public Health and Family Medicine, 2016)
Background: The prevalence of HIV was greater than 30% in the Free State province in South Africa and PMTCT services were widely available at the time the guidelines recommended nevirapine in labour and to the child postpartum. Aim: The aim was to determine the effectiveness of the PMTCT program in the Free State by measuring HIV transmission and HIV-free survival in children less than two years of age. Variables associated with HIV transmission and HIV-free survival including PMTCT uptake by mother, demographic characteristics, type of delivery and breastfeeding status were investigated. Methods: This was a secondary analysis of data collected from a cross sectional community household survey, using multistage cluster sampling. The population was all women who had given birth to a child in the two years prior to the study in the catchment area of three sub-districts that were randomly selected in Free State. All mothers were anonymously tested for HIV and if infected the child was also tested. Trained field workers interviewed mothers, identified children who had died and collected data on variables that could be related to transmission and survival. Logistic regression was used to determine risk factors.